2015
DOI: 10.3389/fmicb.2015.01252
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Culturable Tea Rhizobacteria Isolated from Tea Estates of Assam, India for Growth Promotion in Commercial Tea Cultivars

Abstract: In the present study, 217 rhizobacterial isolates were obtained from six different tea estates of Assam, India and subjected to preliminary in vitro plant growth promotion (PGP) screening for indole acetic acid (IAA) production, phosphate solubilization, siderophore production and ammonia production. Fifty isolates showed all the PGP traits and five isolates did not exhibit any PGP traits. These 50 potential isolates were further analyzed for quantitative estimation of the PGP traits along with the aminocyclop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 52 publications
2
59
0
1
Order By: Relevance
“…amounted to 3-7 and 16 µg mL −1 , respectively. Dutta et al [32] showed IAA production of 87.9 µg mL −1 for Bacillus sp. In turn, Morel et al [33] proved that Delftia sp.…”
Section: Discussionmentioning
confidence: 99%
“…amounted to 3-7 and 16 µg mL −1 , respectively. Dutta et al [32] showed IAA production of 87.9 µg mL −1 for Bacillus sp. In turn, Morel et al [33] proved that Delftia sp.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of ACCD bacteria equipped with such features to benefit host plants has been demonstrated in several studies (Sachdev et al, 2009; Karthikeyan et al, 2012). Inoculation of IAA-producing bacteria promotes root growth by increasing number and length of adventitious root as well as by altering root architecture that lead to enhanced nutrient uptake (Chakraborty et al, 2006; Yang et al, 2009; Dutta et al, 2015), which in turn promotes plant growth (Chakraborty et al, 2006; Yang et al, 2009; Dutta et al, 2015). Similarly, phosphate solubilization is an important attribute of rhizospheric microorganism that provides the bio-available phosphate for improvement of plant growth (Liu et al, 2014; Dutta et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The tea clones were treated with 10 ml cell suspension by soil drenching at one-month intervals for three months and watered with sterile distilled water daily (Liotti et al, 2018;Zhao et al, 2018). All vegetative parameters such as shoot length, root length, shoot fresh and dry weight and root fresh, dry weight, chlorophyll content and soil parameter analysis were recorded and compared to control (Dutta et al, 2015b;Dutta and Thakur, 2017).…”
Section: Preparation Of Actinobacterial Inoculum and Treatmentmentioning
confidence: 99%
“…To date, rhizospheric and endophytic PGP bacteria have been explored and characterized from C. sinensis (Dutta et al, 2015b;Nath et al, 2015;Dutta and Thakur, 2017). However, very few data are available on tea endophytic actinobacteria especially in the North East region of India.…”
Section: Introductionmentioning
confidence: 99%